Characterization of genes coding for Bacillus thuringiensis ssp. medellin toxic proteins - RESTREPO, NORA HELENA; PATIÑO, MARÍA MERCEDES; ORDUZ, SERGIO; DÍAZ, THAIS; ROJAS, WILLIAM (Revista Colombiana de Entomología, 1996)
Resistance to Bacillus thuringiensis (Bt) toxins in Lepidoptera and Diptera insects has been showed under laboratory environments and in 1990 it was reponed by the first time under field conditions. Therefore, it is important to characterize the new toxíc proteins and identify their genes in the recently discovered strain of Bacillus thuringiensis ssp. medellien (Btmed), with mosquito larvae activity. The generation of a genomic library of Btmed allowed the isolation of the toxins genes and their initial characterization. In order to make the genomic library of Btmed in the lambda ZAP II vector, the total DNA of Btmed was isolated and a partial restriction was performed with EcoRI. The library was screened using immunodetection techniques. The purified immunoreactive clones displayed an insert of approximately 4 Kilobases (Kb) which encoded a protein of a molecular weight of 100 Kilodalton (KDa) that shows toxic activity against mosquito larvae.